2022
DOI: 10.1186/s12978-022-01411-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnoses and procedures of inpatients with female genital mutilation/cutting in Swiss University Hospitals: a cross-sectional study

Abstract: Background Female genital mutilation/cutting (FGM/C) can result in short and long-term complications, which can impact physical, psychological and sexual health. Our objective was to obtain descriptive data about the most frequent health conditions and procedures associated with FGM/C in Swiss university hospitals inpatient women and girls with a condition/diagnosis of FGM/C. Our research focused on the gynaecology and obstetrics departments. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Thus, in addition to violating a fundamental human right, FGM also leads to anxiety, depression, and social isolation 3 , 4 . Furthermore, it is also associated with short-term and long-term complications, including bleeding, infection, dermoid cysts and abscesses, chronic pelvic pain, recurrent urinary tract infections, difficulties in menstruation, maternal and fetal issues, and dyspareunia 6 . It was also noted that the severity of these complications correlated with the type of FGM 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in addition to violating a fundamental human right, FGM also leads to anxiety, depression, and social isolation 3 , 4 . Furthermore, it is also associated with short-term and long-term complications, including bleeding, infection, dermoid cysts and abscesses, chronic pelvic pain, recurrent urinary tract infections, difficulties in menstruation, maternal and fetal issues, and dyspareunia 6 . It was also noted that the severity of these complications correlated with the type of FGM 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is also associated with short-term and long-term complications, including bleeding, infection, dermoid cysts and abscesses, chronic pelvic pain, recurrent urinary tract infections, difficulties in menstruation, maternal and fetal issues, and dyspareunia 6 . It was also noted that the severity of these complications correlated with the type of FGM 6 . Fite et al reported that women with FGM had lower sexual desire, less sexual satisfaction, and a higher risk of dyspareunia than other women 3 .…”
Section: Introductionmentioning
confidence: 99%
“…FGM which is defined as cutting and removing all or a part of the clitoris to removing the large lips of the external genitalia, is almost traumatized and without any health advantage ( 5 , 6 ) and the range of its complications is not only physical (from bleeding, infection to death), but psychological (such as anxiety and post-traumatic stress) and also sexual ( 7 , 8 ). Urinary infections, sexual transmitted diseases, bleeding after intercourse, necrotizing fasciitis and long-term side effects in the form of ascariasis, genital lesion, dyspareunia, and infertility, labor and delivery disorders, and reducing the quality of sexual relations are some complications of female mutilation ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%